A perspective on twisted light from on-chip devices - Hui Yang (AIP Publishing LLC, 2021)
Twisted light, with spatially varying phase or polarization, has given rise to various applications, such as micro-particle manipulation, optical communication, and quantum information processing. In recent decades, to bring these applications into reality, various configurations such as conventional spiral phase plates, computer-generated holograms, metasurface-based setups, and on-chip devices have been explored for twisted light generation. In this Perspective, we focus on recent progress in generation twisted light from typical on-chip devices such as waveguides, plasmonic nanoslits, whispering gallery mode configurations, and meta-gratings. We aim at highlighting the key research advances and technical challenges in on-chip twisted light generation. Finally, we outlook the likely future trend of this emerging research field.